ICT and international corporate taxation: tax attributes and scope of taxation - Anne Schäfer; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
In this paper, an outline of the consequences of the increased use of ICT on international corporate taxation, namely on the tax attributes and the scope of taxation, is given. It is argued that the concept of capital export neutrality shall prevail, as it is deemed to be the most appropriate to the changed economic structure. With regard to the tax attributes in the source state, an enlargement of the notion of a permanent establishment in order to shift tax revenues to the source state is not recommendable. Concerning the tax attributes in the residence state, it is shown in how far problems might arise and which alternatives might constitute a solution. As regards the scope of taxation, we recommend that international corporate taxation shall be based on taxation according to the residence principle.
Keywords: H26; H25; H21; 330; International Corporate Taxation; Efficiency; Electronic Commerce; Information and Communication Technologies; Unternehmensbesteuerung; Internationales Steuerrecht; E-Business; Virtuelles Unternehmen; Besteuerungsgrundsatz; Ursprungslandprinzip; Welt; OECD-Staaten